Optimization of Waqf Development through the Quadruple Helix Model for Social and Economic Development in Dayah Malikussaleh North Aceh District - Mukhlis Mukhlis; Muhammad Syukri Albani Nasution; Chuzaimah Batubara (Universitas KH. Abdul Chalim Mojokerto, 2025)
The problem in this research focuses on the suboptimal development of waqf in Dayah Malikussaleh, North Aceh Regency, due to the lack of integration between local government, academics, waqf management institutions, and civil society. The problem formulation studied includes: (1) The role of local government in integrating stakeholders for waqf development; (2) How to increase the active role of all stakeholders through the quadruple helix model; (3) Effective strategies that can be implemented by the government, business people, educational institutions and the community in developing waqf; (4) Evaluation of the positive impact of the quadruple helix model in managing waqf on the social and economic development of society. The research method used is a qualitative study with a descriptive approach. Data was collected through in-depth interviews, observations, and document studies involving various stakeholders, including local government, academics, waqf management institutions, and the community. The research results show that local governments play a strategic role in integrating various stakeholders for waqf development. Through discussion forums and outreach, the government unites the vision of all parties following the Stakeholder Theory.